Engineering production of functional scFv antibody in E. coli by co-expressing the molecule chaperone Skp - Wang, Rongzhi; Xiang, Shuangshuang; Feng, Youjun; Srinivas, Swaminath; Zhang, Yonghui; Lin, Mingshen; Wang, Shihua (Frontiers in Cellular and Infection Microbiology, 2013)
Single-chain variable fragment (scFv) is a class of engineered antibodies generated by the fusion of the heavy (VH) and light chains (VL) of immunoglobulins through a short polypeptide linker. ScFv play a critical role in therapy and diagnosis of human diseases, and may in fact also be developed into a potential diagnostic and/or therapeutic agent. However, the fact that current scFv antibodies have poor stability, low solubility and affinity, seriously limits their diagnostic and clinical implication. Here we have developed four different expression vectors, and evaluated their abilities to express a soluble scFv protein. The solubility and binding activity of the purified proteins were determined using both SDS-PAGE and ELISA. Amongst the four purified proteins, the Skp co-expressed scFv showed the highest solubility, and the binding activity to antigen TLH was 3-4 fold higher than the other three purified scFv. In fact, this scFv is specific for TLH and does not cross-react with other TLH-associated proteins and could be used to detect TLH directly in real samples. These results suggest that the pACYC-Duet-skp co-expression vector might be a useful tool for the production of soluble and functional scFv antibody.